Modeling the Nigerian inflation rates using periodogram and Fourier Series Analysis - Chukwuemeka O. Omekara; Emmanuel J. Ekpenyong; Michael P. Ekerete (CBN Journal of Applied Statistics, 2013)
This work considers the application of Periodogram and Fourier Series Analysis to model all-items monthly inflation rates in Nigeria from 2003 to 2011. The main objectives are to identify inflation cycles, fit a suitable model to the data and make forecasts of future values. To achieve these objectives, monthly all-items inflation rates for the period were obtained from the Central Bank of Nigeria (CBN) website. Periodogram and Fourier series methods of analysis are used to analyze the data. Based on the analysis, it was found that inflation cycle within the period was fifty one (51) months, which coincides with the two administrations within the period. Further, appropriate significant Fourier series model comprising the trend, seasonal and error components is fitted to the data and this model is further used to make forecast of the inflation rates for thirteen months. These forecasts compare favourably with the actual values for the thirteen months.
Keywords: E31; E37; 330; Fourier series analysis; periodogram; frequency domain; time series; forecasting